2016
DOI: 10.1530/joe-16-0206
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine effects of duodenal–jejunal exclusion in obese patients with type 2 diabetes mellitus

Abstract: Duodenal-jejunal bypass liner (DJBL) is an endoscopically implantable device designed to noninvasively mimic the effects of gastrointestinal bypass operations by excluding the duodenum and proximal jejunum from the contact with ingested food. The aim of our study was to assess the influence of DJBL on anthropometric parameters, glucose regulation, metabolic and hormonal profile in obese patients with type 2 diabetes mellitus (T2DM) and to characterize both the magnitude and the possible mechanisms of its effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…This form of reversible bariatric procedure has been shown to reduce weight and improve glycaemic control in patients with diabetes and obesity. [2][3][4][5] REVISEDiabesity (Randomisation to Endobarrier alone Versus with Incretin analogue in SustainEd Diabesity), an Association of British Clinical Diabetologists (ABCD) UK-funded, multicentre, randomised controlled trial (ISRCTN00151053) led by our institution supports these observations. Additionally, preliminary data on the first year of treatment with the EndoBarrier device combined with liraglutide therapy showed benefit on HbA1c and weight/body mass index (BMI), liver fat and cardiovascular risk, as measured by the UK Prospective Diabetes Study (UKPDS) risk engine v2.…”
Section: Introductionmentioning
confidence: 63%
“…This form of reversible bariatric procedure has been shown to reduce weight and improve glycaemic control in patients with diabetes and obesity. [2][3][4][5] REVISEDiabesity (Randomisation to Endobarrier alone Versus with Incretin analogue in SustainEd Diabesity), an Association of British Clinical Diabetologists (ABCD) UK-funded, multicentre, randomised controlled trial (ISRCTN00151053) led by our institution supports these observations. Additionally, preliminary data on the first year of treatment with the EndoBarrier device combined with liraglutide therapy showed benefit on HbA1c and weight/body mass index (BMI), liver fat and cardiovascular risk, as measured by the UK Prospective Diabetes Study (UKPDS) risk engine v2.…”
Section: Introductionmentioning
confidence: 63%
“…The methodology and outcomes of the performed DJBL study have been described in detail elsewhere . Briefly, 30 obese T2DM individuals (20 males, 10 females, aged 33‐65 years, HbA 1C > 53 mmol/mol) were subjected to 10 months of treatment with DJBL.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the weight loss associated with DJBL implantation, a combination of neuroendocrine and metabolic mechanisms has been proposed, including a reduced secretion of diabetogenic hormones in the proximal intestine due to the lack of nutrients‐induced stimuli (foregut hypothesis), or an increased secretion of incretins in response to undigested food in the distal small intestine (hindgut hypothesis) . More recently, changes in other gut hormones and bile acids along with their regulator fibroblast growth factor 19 have also been implied …”
Section: Introductionmentioning
confidence: 99%
“…Small prospective studies have demonstrated promising improvements in diabetes control and loss of body weight . To obtain prospective data in a larger cohort of patients, the ENDO Trial, a multicentre, double‐blind, randomized trial, was conducted to evaluate the safety and efficacy of the DJBL.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Small prospective studies have demonstrated promising improvements in diabetes control and loss of body weight. [11][12][13][14][15][16][17][18][19][20][21] To obtain prospective data in a larger cohort of patients, the ENDO Trial, a multicentre, double-blind, randomized trial, was conducted to evaluate the safety and efficacy of the DJBL. However, in March 2015, the US FDA discontinued enrollment of patients because of complications in the form of 7 hepatic abscesses.…”
Section: Introductionmentioning
confidence: 99%